Uncovering the initial nucleation process during rapid heating of Fe-Co-Nb-B metallic glasses - Löfstrand, Julia; Tidefelt, Mattias; Fisk, Martin; Kaplan, Maciej; Sahlberg, Martin; Han, Xiaoliang; Kaban, Ivan; Jönsson, Petra E. (Materials and Design, 2025)
Fe-based metal amorphous nanocomposites, consisting of dispersed nanocrystallites within an amorphous metallic glass matrix, are used as low-loss soft-magnetic components in energy conversion devices. The nanocrystallites are formed by partial devitrification of the amorphous matrix and the properties of the composite are a result of the devitrification process. Understanding the rate-dependent crystallisation kinetics is therefore essential for tailoring the properties of such nanocomposites. In this study, we monitor the devitrification process in situ during rapid heating of metallic glasses with composition (Fe0.75Co0.25)95−xNb5Bx, x=15, 20 at.%, by using high-energy wide angle X-ray scattering. The results are compared to samples devitrified at low heating rates, analysed using differential scanning calorimetry, X-ray diffraction, and magnetometry. Additionally, we present a model describing the crystallisation kinetics based on classical nucleation and growth theory coupled with thermodynamic data for a generalised Fe-B system. The model successfully reproduces the onset of devitrification as a function of time, temperature, and B-concentration, thereby providing valuable insights for the design of advanced soft-magnetic metal amorphous nanocomposites.
Keywords: CALPHAD; Classical nucleation and growth theory (CNGT); HITPERM; Magnetic properties; Metal amorphous nanocomposite (MANC)